HANDLING OF SYRINGE SHARPS IN A NON-INCINERATION HEALTH CARE WASTE DISPOSAL - Mwinuka, Tito E.; Nyichomba, Bavo B. (Tanzania Journal of Engineering and Technology, 2018)
An attempt has been made by the R&D team of the University of Dar es Salaam to design and manufacture two needle cutter prototypes, a manually operated and an automatic needle cutter to be used in rural and urban areas, respectively. This is part of the UNDP and WHO efforts aimed at promoting the non-burn medical waste disposal technologies in developing countries such as Argentina, India, Latvia, Lebanon, Philippines, Senegal, Tanzania and Vietnam. The project also involves designing and manufacturing of the autoclaves for sterilizing of needle cutters and other infectious medical waste. The use of needle cutters in hospitals is aimed at cutting the needles off from syringes hence eliminating the possibility of being re-used as may be the case if they are just buried in landfills. The needles and plastic barrels of the syringes are then sterilized at 121 o C in an autoclave before disposing them in land-fills or recycling them. It should be noted that unlike manual needle cutters, automatic needle cutters do not add a step in administering injection and hence they are likely to be accepted by nurses and health care authorities. Two types of automatic cutter prototypes were developed by UDSM R&D Team; one using pneumatic mechanisms and the other one using a 12V- DC motor to cut the syringe needles and to push the plastic barrel into the waste container. Of the two, the 12V-DC motor operated mechanism was found to be affordable and suitable for use in rural areas also since it can easily use solar power. The above prototypes have already been manufactured and tested and found to be working properly. Views of various stakeholders were used to improve and perfect the designs. The costs of these prototypes are estimated to be USD 50 and 150 for manually operated needle cutter and 12V-DC operated needle cutter, respectively. These technologies, except the automatic needle cutters, have already been disseminated to local producers so as to be able to manufacture the same in mass production and at much more affordable costs. Training on the use of non-burn technologies including management of medical waste is essential for successful implementation of these technologies. There is a need also to sensitize the Government, Municipal Authorities and Healthcare Authorities including hospitals on non-burn disposal of medical waste for the project to be successful.